En torno a la educación, el humanismo y las humanidades - Munizaga, Roberto (Revista Chilena de Humanidades, 2015)
The author examines sorne trends in Chilean education at the beginning of this century, analysing the later impact of European ideas and orientations under the influence of two world wars. He centers his work on the relations between culture, humanism and education, stressing the primacy of man as a whole being based on these three factors that are of his very essence. Within these terms, the Humanities constitute the spirit of fulfillment of man together with its prolongations in the sciences and its occupational structures, in an everincreasing process of communication and need of dialogue.